Lupus Nephritis in a Patient with Sickle Cell Disease - Vinay Minocha; Fauzia Rana (Case Reports in Hematology)
Introduction. The diagnosis of systemic lupus erythematosus (SLE) in patients with sickle cell disease (SCD) can be difficult to establish because the musculoskeletal, central nervous system, and renal manifestations are similar in both diseases. In the presented case, we highlight the diagnostic challenge that can evolve in patients with a concurrence of both diseases and we establish the importance of early recognition and treatment of lupus nephritis in patients with SCD. Case Presentation. We present a case of a 31-year-old African American female with sickle-C disease (hemoglobin SC) who was admitted to our hospital with complaints of periumbilical abdominal pain associated with intractable nausea and vomiting, abdominal distension, and worsening lower extremity edema. Urine studies revealed nephrotic range proteinuria and the immunological investigations were consistent with lupus. A renal biopsy revealed focal proliferative lupus nephritis. Conclusion. It is important to consider the presence of a coexisting autoimmune disease in a patient with sickle hemoglobinopathy who displays an atypical and multisystem presentation that is unresponsive to conventional therapies. When a significant kidney disease is present, a renal biopsy is critical in identifying the etiology of a renal abnormality in the setting of coexisting SLE and SCD.